Peranan Retribusi Sektor Pariwisata terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Kotabaru - Prasetia, Adi; Sa’roni, Chairul (PPJP ULM, 2019)
The purpose of this study is to determine the role of retribution in the tourism sectorto the Local Revenue in Kotabaru District. In this research using quantitativedescriptive method. The type of data used in the form of secondary data about thedevelopment of the retribution of the tourism sector to the Local Revenue in KotabaruDistrict. The results of research can be used by local governments to set policies on thetourism sector to increase the local revenue.Based on the results of this study, it is indicated that the role of tourism retribution isstill relatively small with respect to the original regional income in Kotabaru Regency due tothe increase in the amount of local revenue with a larger amount.